MOTIVASI DAN AKIBAT PRILAKU KEJAHATAN MANUSIA DITINJAU DARI ANALISIS PERSONAL DAN SOSIAL - Suaidi Suaidi (JURNAL ILMIAH RESEARCH STUDENT, 2024)
The development of crime from time to time always increases, due to several factors that influence it, various theories and efforts to tackle crime various elements are involved, but crime with its various developments keep pace even faster with the development of theories and countermeasure systems. The rule of law is like a meaningless slogan, it is precisely crime that develops in a state of law. Factors that influence the occurrence of crime due to innate and environmental factors. For this reason, the development of crime can be suppressed by preventive measures that lead to personal development and environmental improvements, both social economic and cultural.